Molecular genetic associations between a prominent serotonin transporter gene polymorphism (5‐HTTLPR/rs25531) and individual differences in tendencies toward autistic traits and generalized internet use disorder in China and Germany - YingYing Zhang; Shuxia Yao; Helena Schmitt; Benjamin Becker; Keith M. Kendrick; Christian Montag (Brain and Behavior, 2022)
Abstract Background The serotonin transporter polymorphism 5‐HTTLPR is an extensively investigated genetic marker of autistic traits or autism spectrum disorder, and recently has also been studied in the realm of internet use disorder (IUD), yet the findings remain controversial. Therefore, the present study aimed to explore associations between 5‐HTTLPR (also including SNP rs25531) and autistic traits/IUD tendencies and to assess whether the relationship between autistic traits and IUD tendencies varies by this genetic marker in participants from China and Germany. Methods A total of 540 Chinese and 563 German subjects were genotyped for 5‐HTTLPR/rs25531 and completed the Adult Autism Spectrum Quotient questionnaire and the short version of the Internet Addiction Test. Results Carriers of the low expressing S'S’ genotype (S, LG) showed significantly higher levels of autistic traits than the high expressing allele (e.g. LA) carriers in both samples. There was no significant effect of 5‐HTTLPR/rs25531 on IUD either in the Chinese or Germany samples, whereas positive correlations between autistic traits and IUD varied by 5‐HTTLPR/rs25531 genotypes and also differed between Chinese and German samples. In the Chinese sample, positive correlations were mainly driven by S'S’ and S'L' carriers, while they were mainly determined by S'L’ and L'L' carriers in the German sample. Further analyses revealed that the associations between autistic traits and IUD tended in parts to be more strongly pronounced in the complete German sample compared to the complete Chinese sample, and also varied depending on 5‐HTTLPR/rs25531 genotypes (in S'S’ carriers: China > Germany; in S'L’ and L'L’ carriers: China < Germany; both in terms of more positive associations). Conclusions Our findings suggest carriers of low expressing alleles (S, LG) are more likely to show higher autistic traits in both Chinese and German samples. Furthermore, the present work shows that both 5‐HTTLPR/rs25531 and cultural differences might be of relevance to understand associations between autistic traits and IUD tendencies, but this needs to be further backed up.